Women's marginalization in Nigeria and the way forward. Issue 5 (20th October 2018) - Bako, Mandy Jollie; Syed, Jawad
ABSTRACT: Marginalization of women in economic development and in social and political spaces is a worldwide phenomenon; however, it is worse in developing countries. In Nigeria, despite the adoption of the United Nations' Convention on the Elimination of All Forms of Discrimination against Women in 1985 and similar local policies, such as the National Gender Policy of 2006, inequality still exists due to a myriad of cultural and structural challenges. This has constrained women's participation in all spheres of life with serious implications for human resource development and, in that capacity, economic development of the country and the general state of gender equality. This article reviews the situation in Nigeria and argues that local adaptation of international norms as well as a focus on domestic reforms in laws and culture might be a reasonable approach towards women's development.